2001
DOI: 10.1054/bjoc.2001.1865
|View full text |Cite
|
Sign up to set email alerts
|

High density oligonucleotide array analysis of interferon-α2a sensitivity and transcriptional response in melanoma cells

Abstract: Summary Interferon alpha (IFN-α) represents an adjuvant therapy of proven effectiveness in increasing disease-free interval and survival in subgroups of melanoma patients. Since high doses of cytokine are required, the treatment is often accompanied by toxic side effects. Furthermore, naturally occurring insensitivity to IFN-α may hamper its therapeutic efficacy. Clinical, molecular or immunological markers enabling the selection of potential responders have not been identified so far. To explore the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…In a different experimental setting, Certa et al (2000) addressed the genetic profile of melanoma cell lines classified according to their sensitivity or insensitivity to Interferon-a treatment. This study represents useful basis to define an extended molecular database of potential relevance both in basic cell biology studies, and in therapeutic options.…”
Section: Cdna Arrays In Melanomamentioning
confidence: 99%
“…In a different experimental setting, Certa et al (2000) addressed the genetic profile of melanoma cell lines classified according to their sensitivity or insensitivity to Interferon-a treatment. This study represents useful basis to define an extended molecular database of potential relevance both in basic cell biology studies, and in therapeutic options.…”
Section: Cdna Arrays In Melanomamentioning
confidence: 99%
“…A study has revealed that IFN induction of IFI 16 in human melanoma cell lines correlates well with inhibition of cell growth (Certa et al, 2001). As the IFI 16 gene is located in the region 1q22, predicted to harbor a senescence gene(s) (Hensler et al, 1994;Karlsson et al, 1996), we investigated the role of IFI 16 in cellular senescence of prostate epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…To date the gene expression profile induced by IFN-␣2 has been studied predominantly in fibrosarcoma and melanoma cell lines (3,4). Little is known about the transcriptional profiles for other cell lines and nontransformed cells or of donorspecific differences.…”
mentioning
confidence: 99%